Erosion of Ethnobotanical Knowledge in the Younger Generation: Level of Student Knowledge of the Use of Medicinal Plants in Culture in North Sumatra - Has, Dini Hardiani; Sari, Ratna; Girsang, Sahat Raja Marogo; Arianda, Dela; Syah, Firman; Oktaviani, Eva; Marpaung, Sutan Sahala Muda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Traditional knowledge preservation is a fundamental component of sustainable development, contributing to biodiversity conservation, community health resilience, and the safeguarding of cultural heritage. North Sumatra Province, Indonesia, with its rich ethnic and cultural diversity, represents an important setting for ethnobotanical research. This study aimed to assess the level of knowledge among the younger generation regarding the use of medicinal plants in traditional medicine, cultural practices, and traditional ceremonies. A quantitative descriptive survey was conducted involving 61 respondents, predominantly university students. Data were collected using a structured questionnaire and analyzed descriptively through frequency and percentage distributions. Most respondents were female (68.85%), aged 17–20 years (63.93%), and belonged to the Toba Batak ethnic group (45.90%). The findings revealed that 41% of respondents had a moderate level of ethnobotanical knowledge, indicating that while most participants possessed basic knowledge of medicinal plants, only 10% were familiar with more than 15 medicinal plant species. Overall, the younger generation demonstrated a moderate level of knowledge; however, the limited recognition of medicinal plant diversity and the low understanding of their cultural and symbolic functions suggest a gradual erosion of traditional ethnobotanical knowledge. These findings provide baseline information for developing educational and cultural preservation programs aimed at strengthening ethnobotanical knowledge among younger generations and supporting the conservation of Indonesia's traditional biocultural heritage.